Officinal medicinal plants of the Nakhchivan Autonomous Republic - Anvar M. Ibrahimov; Alex V. Matsyura (Acta Biologica Sibirica)
The Nakhchivan Autonomous Republic, situated at the crossroads of Mediterranean, Western Asian, and Iranian floras, is home to a rich diversity of medicinal plants. Approximately 132 species of officinal medicinal plants have been identified, with 44 cultivated and 88 wild-growing species. This region's flora contributes significantly to both traditional and scientific medicine, with many species documented in pharmacopoeias over the past 137 years. The escalating global demand for herbal remedies and natural health products underscores the importance of these plants, yet they face threats from habitat destruction, over-harvesting, and climate change. This study aims to assess the species composition, distribution, and conservation status of medicinal plants in the Nakhchivan Autonomous Republic. It focuses on understanding their habitats, ecological conditions, and the traditional knowledge associated with their use. Field expeditions conducted from 2015 to 2021 involved the collection of herbarium specimens and the identification of species using established botanical references. The study employed Geographic Information Systems (GIS) for mapping plant distributions and assessing biodiversity hotspots. The Conservation Priority Index (CPI) was calculated for each species, incorporating biological scores and risk of use scores to classify species into three conservation categories. The study identified 132 officinal medicinal plant species across 47 families and 105 genera. The most represented families include Rosaceae, Asteraceae, and Fabaceae. Among these, several species are classified as endangered, including Adiantum capillus-veneris and Juniperus sabina. The research also documented the traditional uses of 59 species in folk medicine, highlighting their cultural significance.